OPTIMIZING THE INTERPERSONAL COMMUNICATION OF ACADEMIC ADVISORS IN SUPPORTING STUDENTS’ STUDY COMPLETION - Choiriyati, Sri; Khomsahrial Romli; fitri yanti; achi rinaldi; rini setiawati (Ath Thariq Jurnal Dakwah dan Komunikasi, 2025)
Higher education in Indonesia, especially at the University of Muhammadiyah Lampung (UMLampung), is a multicultural system, where students come from various cultural, ethnic, and religious backgrounds. This diversity poses challenges in interpersonal communication between lecturers and students, especially in the context of the role of Academic Supervisors (PAs). Effective interpersonal communication is an important element in creating a harmonious learning environment and supporting academic success. This study aims to explore the role of PA lecturers in optimizing interpersonal communication to support the completion of student studies of the Communication Science Study Program at the Faculty of Social and Political Sciences (FISIP) UMLampung. The approach used is qualitative descriptive research with data collection through observation, interviews, and documentation. The results of the study show that the role of PA lecturers in interpersonal communication is very important, both in providing appropriate academic information, directing students in completing assignments, and helping to overcome problems faced by students. PA lecturers who are able to communicate effectively with students from diverse cultural backgrounds, can create supportive relationships, which contribute to the timely completion of studies. However, there are still obstacles such as time constraints and access difficulties between PA lecturers and students that need to be considered to optimize this role. This study suggests the importance of improving PA lecturers' interpersonal communication skills in order to create a more inclusive learning atmosphere and support the achievement of students' academic goals.